Global citizenship education in teacher education theoretical and practical issues - Schugurensky, Daniel 1958-; Wolhuter, Charl (Routledge, Taylor & Francis Group, 2020)
"Global Citizenship Education in Teacher Education explores the role of teacher education in formulating a practice of citizenship that has a global scope and is guided by critical and emancipatory approaches. By considering global challenges and crisessuch as mass poverty and rising levels of inequality, growing streams of international migration, and excesses of the neo-liberal economic revolutionthis book provides a valuable analysis for researchers in the fields of teacher education, comparative and international education, and globalization studies. By examining historical and conceptual issues surrounding the incorporation of global citizenship education (GCE) into teacher education, and by presenting examples from across the world, this volume enhances the power of GCE to transform education on an international scale."--Provided by publisher
Keywords: Teachers / Training of; World citizenship / Study and teaching; Teachers; Education; Comparative education; Citizenship; EDUCATION / General; EDUCATION / Philosophy & Social Aspects; EDUCATION / Comparative; Electronic books